Malen'kaia Vera - Pichul, Vasili (Soviet Union, 1988)
During the late '80s in Gorbachev's Soviet Union most films took advantage of the liberalizing climate to address problems and realities that were often ignored in more oppressive times. Little Vera is one result. The story of a young rebellious girl in a disfunctional Russian family confronted with adult decisions
Keywords: Fiction films